Technology, Participation and Bodily Interactions in Nature: The Potential of Mobile Technology in Situated Learning - Balling, Gitte; Schilhab, Theresa; Lynge Esbensen, Gertrud (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
In this study, we test and discuss a Danish communication and entertainment mobile application (app) aimed at children aged 10 to 12 years for use by families and schools. The app, Tidslommen, has been developed by Museum Vestsjælland, a collaboration among natural history museums in Denmark. Tidslommen features audio and video guides and augmented reality with game elements, which become active when users enter specific geographical spots. Adopting a transdisciplinary approach (media study, studies in children’s culture, educational neuroscience, educational anthropology) and using a combination of the walkthrough method and sensory ethnography, we explore the functionalities of the app at four locations. With our field-based user experiences as the point of departure, we analyse and discuss the potential and challenges related to the intersections among bodily and nature-based experiences, mobile technology and participatory practices as part of a didactic setting that aims to encourage children to participate in experiences with nature. Our study suggests that using mobile technology encourages interactions between peers and moving around at a location. The app also allows for an individualised experience characterised by a play-oriented approach to the location.